(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
It’s a web based named as “online voting system” which aims to develop a computerized system to make the election process more secure and user friendly. This system has many features which are generally not available in current days. With the help of this system, user can cast their vote without going to any polling booth; it can save their time and effort. This system can also save money of government which is spent in preparation of election process. This system uses face detection and recognition technology to make this system more secure and safe. Overall this project of ours is being developed to help staff of Election commission of India and also reduce the human efforts.